1903
DOI: 10.1007/bf01946269
|View full text |Cite
|
Sign up to set email alerts
|

Über Myopie

Abstract: I. Assistenten an der Augenklinik zu Jena. Mit 15 Figuren im Text. Der yon Donders aufgestellte Satz ,,Ein myopisches Auge ist kein gesundes Auge; dieselben Ursachen, wetche zur Myopie Veranlassung geben-insbesondere angestrengte Naharbeit-, beg~instigen aueh ihre weitere Entwieklung", hat bekanntlieh durchaus nieht allgeraeine Anerkennung gefunden. Konnte aueh nach den ausgedehnten statistischen Untersuchungen naraentlieh yon H. Cohn der direkte Zusammenhang zwischen aDgestrengter Naharbeit und Aehsenmyopie n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1930
1930
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Similarly, we found a higher incidence of RRDs in one small subset—young females. Though, the overall incidence of RRDs in those under age 10 is low, as with previously reported ranges of 0.4 to 2.9 cases per 100,000 in this population 19 , 20 , 36 40 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, we found a higher incidence of RRDs in one small subset—young females. Though, the overall incidence of RRDs in those under age 10 is low, as with previously reported ranges of 0.4 to 2.9 cases per 100,000 in this population 19 , 20 , 36 40 .…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with prior reports and is likely due to higher mean axial length. Dating back to 1903, Hertel et al found that of 6,863 myopes presenting to his eye clinic, 71.5% were male, 85.9% of whom had presented with an RRD as compared to 73.1% of women 36 . In contrast to this and most other reports, Willis et al found that upon multivariate analysis (adjusting for age and sex) the odds of high myopia was actually 1.7 times higher among women than men (adjusted OR, 1.66; 95% CI 1.24–2.24) 9 .…”
Section: Discussionmentioning
confidence: 99%